The use of information technology of eaudit system on audit quality - Ida Farida, Taufiq Supriadi, Mulyani.S, Eddy Mulyadi Soepardi, (Opción, 2019)
This research was conducted to determine an effect of the use of information technology and successful implementation of e-audit systems on audit quality via descriptive and verificative statistical analysis using statistical tool. As a result, the use of information technology does not affect audit quality while the successful implementation of e-audit systems have an effect on audit quality. In conclusion, the successful implementation of the e-audit system on Audit Quality has not been fully qualified as the implementation of the e-audit system is reflected by the efficiency and effectiveness of the inspection process.